2016
DOI: 10.1038/srep27991
|View full text |Cite
|
Sign up to set email alerts
|

FACS-sorted putative oogonial stem cells from the ovary are neither DDX4-positive nor germ cells

Abstract: Whether the adult mammalian ovary contains oogonial stem cells (OSCs) is controversial. They have been isolated by a live-cell sorting method using the germ cell marker DDX4, which has previously been assumed to be cytoplasmic, not surface-bound. Furthermore their stem cell and germ cell characteristics remain disputed. Here we show that although OSC-like cells can be isolated from the ovary using an antibody to DDX4, there is no good in silico modelling to support the existence of a surface-bound DDX4. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…However, whether FGSCs exist has aroused widespread controversy between supporters and opponents in recent years [10, 19, 21, 32, 33]. In 2009, since Wu et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whether FGSCs exist has aroused widespread controversy between supporters and opponents in recent years [10, 19, 21, 32, 33]. In 2009, since Wu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to somatic cells in the ovary, there are relatively few FGSCs (0.014%) in ovaries [11], and utilizing an inappropriate molecule to label putative germline stem cells, could lead to failure in isolating FGSCs [10, 19, 22, 34, 43]. Although Wu's group has used Fragilis-Based MACS to improve the efficiency of FGSC purification [44], Fragilis is also present in the oviduct, stromal cells and oocytes, confirming that this germline marker is not germline-specific [19]. Thus, the limiting factor for the study of FGSC behaviour and characteristics in vitro has been separation and purification of these cells while maintaining their self-renewal ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online transmembrane domain predictors were used on both the human and mouse Ddx4 protein, finding no evidence of a transmembrane region of human Ddx4 that could be used to isolate cells. One model predicted an extracellular domain in mice, but the overall evidence of a transmembrane Ddx4 region that could be isolated using antibodies was weak (Zarate-Garcia et al 2016). Further investigation found that Ddx4 detection may be falsely identifying cells that do not express Ddx4 (ZarateGarcia et al 2016).…”
Section: Are Data Describing Oscs Comparable Between Species?mentioning
confidence: 99%
“…Although the ratio of sorted OSCs after FACS or MACS was low in these studies, OSCs proliferated with the expression of both germ cell and stem cell markers during culture, and contributed to oocytes after grafting in ovaries ex vivo . However, the use of an MVH antibody in a live-cell sorting assay to detect antigens on the cell surface is questionable because MVH is a germline-specific RNA helicase and is believed to exist in the cytoplasm 13,25,108. Several attempts to resolve this issue with the MVH antibody approach have been reported using an SSEA-1 antibody or Ddx4-cre transgenic mice 42,75.…”
Section: Future Perspectives For Pgc Culturementioning
confidence: 99%